Le Cygne by Charles Baudelaire: The Emergence of the Between-worlds Allegory from the flânerie - Oliveira, Andressa Cristina de [UNESP]; Eduardo, Thais de Carvalho [UNESP] (Univ Fed Minas Gerais, Dept Filosofia & Ciencias Humanas, 2023)
Since its origin, walking as an aesthetic practice has been strictly linked to idleness, and this characteristic allows the privilege of doing it through the rhythm of wandering. This practice has a very strong link, above all, with human symbolic production since the beginning. Thus, it fits into a symbolic and liberating attitude for the walker. In this work, we aim to analyze how the sum of metaphors, from which the whole meaning of Baudelaire's historical modernity emerges, materialized in the allegory of the Swan as a poet and exiled in his own time, is presented in the poem Le Cygne (The Swan) published in Tableaux Parisiens section of the second edition of Fleurs du mal in 1861 in the light of Benjamin's (1984, 2009, 2019) and Hanson's (2006) interpretation of allegories and of Hazan's (2017) studies on the urban transformation of Paris in the 19th century.
Keywords: Walk; Baudelaire; Flanerie; Wanderlust; Modernity; Allegory